Kajian Semiotik Pertunjukan Dalam Performa Drama “Balada Sakit Jiwa” - Misnawati Misnawati; Petrus Poerwadi; Apritha Apritha; Anwarsani Anwarsani; Siti Rahmawati (Universitas Palangka Raya, 2022)
Performance Semiotics in Dramatic Performance is a study of the semiotics of theater or stage performances related to the theory of signs and sign systems in the performing arts called theater. Theater semiotics tries to understand the components of theater and establishes the assumption that everything within the framework of theater is a sign or sign. Theatrical performances are essentially a series of sign systems. This study aims to: (1) reveal the process of creating and presenting the performance art of the Mental Ill Ballad Drama, (2) reveal signs related to the activities of the Mentally Ill Ballad Drama performance actors, (3) reveal signs related to the appearance of the Mentally Ill Ballad Drama performance actors Jiwa, (4) reveals signs related to the spatial aspect or place of the performance of the Mentally Ill Ballad and (5) reveals signs related to the non-verbal acoustic aspects of the Mentally Ill Ballad's performance. This research was carried out at the Campus of the Indonesian Language and Literature Education Study Program, Department of Language and Arts Education, FKIP, Palangka Raya University, Central Kalimantan Province. The object of research is students who practice theater and perform theater. This study involved (1) lecturers who taught the Drama/Theatre Performance course, (2) drama/theatre arts workers, and (3) students who practiced and performed plays/theatre. Data collection techniques in this field research are observation, recording, recording, and interviews. The collected data will be analyzed using the theory of Performance Semiotics. The performance semiotics contained in the performance of the drama Balada Illness, are: (1) signs related to the process of creating and presenting performing arts, (2) signs related to actor activities, (3) signs related to actor appearances, (4) signs related to spatial aspects, and (5) signs related to non-verbal acoustics.